Pengaruh Waktu Fermentasi Terhadap Kadar Protein Dari Tempe Biji Buah Lamtoro Gung (Leucaena leucocephala) - Muthmainna, Muthmainna; Sabang, Sri Mulyani; Supriadi, Supriadi (Jurnal Akademika Kimia, 2016)
Lamtoro gung (leucaena leucocephala) is one of the food materials containing high enough protein which allow to be used as raw material for producing tempeh through fermentation. This study aimed to determine the effect of fermentation time to the protein levels of lamtoro gung seeds tempeh with variation fermentation times of 24, 36, 48, 60 and 72 hours. Steps in this study were sample preparation, producing lamtoro gung seeds tempeh,and protein levels analysis. The protein level was determined by Kjeldahl method. The results showed that there was an effect of fermentation time to the protein levels. The longer the fermentation time took effect to the lower the levels of protein produced. The highest protein level was obtained at 24 hours of fermentation time that was equal to 7.943%, while the protein level on fermentation time of 36 hours was equal to 7.725%, 48 hours fermentation time was equal to 7.195%, 60 hours fermentation time was equal to 7.197%, and 72 hours fermentation time was equal to 5.733%.